Penyelewengan Kitab Taurat dan Penjelasannya di dalam Al-Qur’an - Abdullah, Mustaffa; Raja Baharudin, RAP Ishkandar Shah (Jurnal Usuluddin, 2000)
The books of the Jewish Bible are divided into three sections, which is the Torah "al-Taurat," Neviim (the books of the Jewish Prophets) and Ketuvim (the sacred writings). According to Jewish tradition, the Torah is ’believed’ as the Word of God despite manyerrors in it. This is because of the Jewish rabbis and scribes who were responsible to change and to give the new interpretation to the Torah.